2023
DOI: 10.1186/s41182-023-00519-7
|View full text |Cite
|
Sign up to set email alerts
|

Public relations strategies employed by the Ghana Health Service to address COVID-19 vaccine hesitancy: a qualitative inquiry

Abstract: Background Strategies for developing and advancing good public relations can be recognized in nearly all fields of life without making an exception for the healthcare industry. In the wake of the COVID-19 pandemic, matters of public health have gathered more force. The importance of effective public relations for improving healthcare is highlighted by the position that immediate access to reliable health information should be the hallmark of a just society. However, the strategies available for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…In the context of COVID-19 vaccination, governments, and experts’ provision of accurate information about the vaccine acts as triggers to encourage active participation in vaccination initiatives [86]. Ghana employed a combination of informative, motivational, and coercive strategies to address vaccine hesitancy [87]. This strategy could have resulted in high cues to action among HCWs, explaining our findings in this study, and this could have resulted in the higher vaccine uptake reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of COVID-19 vaccination, governments, and experts’ provision of accurate information about the vaccine acts as triggers to encourage active participation in vaccination initiatives [86]. Ghana employed a combination of informative, motivational, and coercive strategies to address vaccine hesitancy [87]. This strategy could have resulted in high cues to action among HCWs, explaining our findings in this study, and this could have resulted in the higher vaccine uptake reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, childhood immunization is a vital component of the country's public health strategy against under‐five morbidity and mortality. The Ghana Health Service (GHS) is responsible for implementing the national immunization program, which aims to provide vaccines to all eligible children [2]. The GHS has developed a comprehensive immunization schedule that includes vaccines against diseases such as measles, polio, tuberculosis, hepatitis B, and yellow fever [2].…”
Section: Introductionmentioning
confidence: 99%
“…The Ghana Health Service (GHS) is responsible for implementing the national immunization program, which aims to provide vaccines to all eligible children [2]. The GHS has developed a comprehensive immunization schedule that includes vaccines against diseases such as measles, polio, tuberculosis, hepatitis B, and yellow fever [2]. Ghana has made considerable progress in increasing childhood immunization coverage rate in recent years.…”
Section: Introductionmentioning
confidence: 99%